How Does Policy Affect the Implementation and Development of Education? Take the Policy of Allocation of Ladder Education Resources in China as an Example (Journal of Education and Development, 2022)
The formation and development of a country's education system are often constrained and guided by the government and policies. Policies that conform to the law of education development and the needs of a wide range of social and economic levels will help the country's education develop steadily and receive positive educational feedback. If the implementation of the policy deviates from the major goal of educational development, and at the expense of the welfare of the majority of people, it will have a lot of negative effects on the education system, and even cause a historical regression of the education system. By analyzing the historical reasons, the current implementation and development of China's ladder educational resource allocation policy, and the impact of regional-specific policies, the author puts forward several facts, solutions, and improvement strategies from the perspective of educational leaders to change the difficulties faced by the policy.